2020
DOI: 10.1029/2020pa003857
|View full text |Cite
|
Sign up to set email alerts
|

A Reassessment of the Chronostratigraphy of Late Miocene C3–C4 Transitions

Abstract: • A change from forest to grassland ecologies began in the late Miocene but chronologies of the published records are based on different time scales. • Recalibration to a consistent time scale demonstrates the diachroneity of the ecological change in different places around the globe. • New constraints link a major C 4 expansion in the late Miocene with evidence for carbon cycle perturbations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 85 publications
(119 reference statements)
2
24
0
Order By: Relevance
“…This study demonstrated that pCO 2 and climate both contributed to the spread of C 4 grasslands and made very specific predictions of where that innovation was favored, but the simulations were colder and had weaker temperature gradients than found in proxy data. The model finds were in general agreement with the diachronous progression of timings found in Tauxe and Feakins (2020). Improving the ability of GCMs to reproduce Miocene climates requires improved paleorecords from regions that are sensitive to CO 2 forcing, but insensitive to differences between Miocene and modern geographic configuration (Bradshaw et al., 2015).…”
Section: Climate Modeling Of the Miocenesupporting
confidence: 84%
“…This study demonstrated that pCO 2 and climate both contributed to the spread of C 4 grasslands and made very specific predictions of where that innovation was favored, but the simulations were colder and had weaker temperature gradients than found in proxy data. The model finds were in general agreement with the diachronous progression of timings found in Tauxe and Feakins (2020). Improving the ability of GCMs to reproduce Miocene climates requires improved paleorecords from regions that are sensitive to CO 2 forcing, but insensitive to differences between Miocene and modern geographic configuration (Bradshaw et al., 2015).…”
Section: Climate Modeling Of the Miocenesupporting
confidence: 84%
“…It has a conformable contact with the overlying Nagri Formation, which consists of greenish-grey medium to coarse-grained sandstone layers with some subordinate claystone intervals. The age of this formation is late Miocene to early Pliocene (Yeats and Hussain 1987;Baker et al 1988;Gee 1989;Tauxe and Feakins 2020). The Nagri Formation is conformably overlain by the Dhok Pathan Formation, the uppermost unit of the Lower Siwaliks.…”
Section: Neogene Stratigraphy Of Potwar Plateaumentioning
confidence: 94%
“…1.5 and 1.6). Recently Tauxe and Feakins (2020) provided updated ages for Siwalik Group sedimentary sections, including the data set of Sanyal et al (2004) from the Northwest Indian region. We also updated sample ages for the data set from the Surai Khola, Nepal section (Section S1.7), and use updated ages for the Pakistani Siwaliks data set (Behrensmeyer et al, 2007;Quade & Cerling, 1995) provided by John Barry and Kay Behrensmeyer on the GTS 2012 timescale.…”
Section: 1029/2020pa004108 6 Of 22mentioning
confidence: 99%